ZmCCT haplotype H5 improves yield, stalk-rot resistance, and drought tolerance in maize - Tong, Lixiu; Yan, Mingzhu; Zhu, Mang; Yang, Jie; Li, Yipu; Xu, Mingliang (Frontiers in Plant Science, 2022)
The ZmCCT locus underlies both stalk-rot resistance and photoperiod sensitivity in maize (Zea mays L.). We previously introduced nine resistant ZmCCT haplotypes into seven elite but susceptible maize inbred lines (containing the haplotype H1) to generate 63 backcross families. Here, we continued backcrossing, followed by selfing, to develop 63 near-isogenic lines (NILs). We evaluated 22 of these NILs for stalk-rot resistance and flowering time under long-day conditions. Lines harboring the haplotype H5 outperformed the others, steadily reducing disease severity, while showing less photoperiod sensitivity. To demonstrate the value of haplotype H5 for maize production, we selected two pairs of NILs, 83B28H1/83B28H5 and A5302H1/A5302H5, and generated F1 hybrids with the same genetic backgrounds but different ZmCCT alleles: 83B28H1 × A5302H1, 83B28H1 × A5302H5, 83B28H5 × A5302H1, and 83B28H5 × A5302H5. We performed field trials to investigate yield/yield-related traits, stalk-rot resistance, flowering time, and drought/salt tolerance in these four hybrids. 83B28H5 × A5302H1 performed the best, with significantly improved yield, stalk-rot resistance, and drought tolerance compared to the control (83B28H1 × A5302H1). Therefore, the ZmCCT haplotype H5 has great value for breeding maize varieties with high yield potential, stalk-rot resistance, and drought tolerance.